Determinants of occupational injuries among building construction workers in Kampala City, Uganda - Arthur Kiconco; Nathan Ruhinda; Abdullah Ali Halage; Stephen Watya; William Bazeyo; John C. Ssempebwa; Joseph Byonanebye (BMC, 2019)
Abstract Background Globally, about 1000 people die and close to 860,000 people sustain injury at work daily. Injury prevention and control require contextual evidence, although most studies in Uganda have focused on general causes. Factors associated with occupational injuries among building construction workers were assessed in this study. Methods A cross-sectional study among building construction workers was conducted in Kampala, Uganda. A standardized semi-structured questionnaire was used to collect data. Three hundred nineteen (319) participants were randomly and proportionately selected from 57 construction sites. Descriptive statistics were used to describe the variables while generalized linear modeling was used to estimate the crude/adjusted prevalence ratios. Results The prevalence of occupational injuries was 32.4%. Most injuries, approximately 70% occurred among nightshift workers. Age of ≤24 years (APR: 2.09 CI: 1.20-3.65, P = 0.009); daily income in or above the second quartile−USD ≥3.2 (APR: 1.72, CI: 1.06-2.80, P = 0.028); job dissatisfaction (APR: 1.63, CI: 1.17-2.27, P = 0.004); job stress (APR: 1.72, CI: 1.22-2.41, P = 0.004); poor safety environment (APR: 1.51, CI: 1.10-2.05, P = 0.009); PPE provision (APR: 1.47, CI: 1.05-2.05, P = 0.02) and routine use of PPE (APR: 0.57, CI: 0.34-0.95, P = 0.03) were significantly associated with occupational injuries. Conclusion There was a relatively high prevalence of injuries mostly resulting from cuts and mostly suffered on night duty. Upper and lower extremities were the most hurt parts of the body during injury leading to loss of a substantial number of productive days. This could affect the health and wellbeing of construction workers. Most of the factors significantly associated with occupational injuries are modifiable thus an opportunity to address the problem. Efforts towards integrating education for behaviour change, advocacy and training workers to demand for their rights to safe and protection at work and legislation enforcement can help reduce occupational injury occurrence.